2016
DOI: 10.1007/s11605-015-3023-9
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Evidence-Based Guidelines in Acute Pancreatitis: an Audit of Practices in University of Toronto Hospitals

Abstract: Despite existing evidence-based practice guidelines for the management of acute pancreatitis, clinical compliance with recommendations is poor. We conducted a retrospective review of 248 patients admitted between 2010 and 2012 with acute pancreatitis at eight University of Toronto affiliated hospitals. We included all patients admitted to ICU (52) and 25 ward patients from each site (196). Management was compared with the most current evidence used in the Best Practice in General Surgery Management of Acute Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…These findings are supported by several clinical practice guideline recommendations even in patients with severe pancreatitis, where it has been shown to maintain the gut mucosal barrier and minimize bacterial translocation 8,9 . However, a previous multicenter audit for assessment of compliance with existing guidelines has shown that compliance with early enteral nutrition is as low as 35% in critically ill patients 58 . Similarly, a national survey of Canadian intensive care units demonstrated that only 50% of centers provided enteral nutrition within the first 48 hours, citing lack of physician support as one of the most important barriers 59 …”
Section: Discussionmentioning
confidence: 55%
“…These findings are supported by several clinical practice guideline recommendations even in patients with severe pancreatitis, where it has been shown to maintain the gut mucosal barrier and minimize bacterial translocation 8,9 . However, a previous multicenter audit for assessment of compliance with existing guidelines has shown that compliance with early enteral nutrition is as low as 35% in critically ill patients 58 . Similarly, a national survey of Canadian intensive care units demonstrated that only 50% of centers provided enteral nutrition within the first 48 hours, citing lack of physician support as one of the most important barriers 59 …”
Section: Discussionmentioning
confidence: 55%
“…As guidelines are required to change current clinical practice, so is the assessment of barriers to adhere to these guidelines. In a recent study on the compliance of guidelines in pancreatitis, it is clear that despite existing evidence-based practice guidelines, the clinical compliance with recommendations is poor [16]. The reasons for this poor compliance in this case are merely speculative but could be related to the different physicians treating these patients.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we expected to find a marked difference in every field between surgeons and gastroenterologists; however, this was not the case. Treatment is becoming more and more a tailor-made decision [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. The use of mesalazine, which is opted by the greater part of participating gastroenterologists, remains a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of patients treated with prophylactic ABs varies in population-based studies across the world from 14% in Portugal [ 42 ], to 25.5% in Canada [ 43 ], 27–58% in the USA [ 44 ], 30.7% in the UK [ 26 ], 81.4% in India [ 45 ], 44.6–69.3% [ 46 ], and 74.3% in Japan [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%